Extreme Hydrological Events: Reflections on the Cabeça D’água Phenomenon in 2021 (Global Journal of Human-Social Science, 2023)
Introduction This investigation aims to study the Cabe a D gua phenomenon which is characterized by a strong rainfall discharge in a certain region in a short period of time In the last few decades worldwide phenomena of extreme precipitation have been presented which occur in countries on different continents and which at the same time have been calling the attention of scientists and scholars in relation to the variations observed in the climate Methodology The data presented were carried out through the Google site for the characterization of the event object of study Results and Discussion It was observed that the phenomenon occurred between the months of July August and September 2021 in countries of all continents Conclusion We concentrated our analysis on the catastrophic events that occurred in China Belgium Germany and Saudi Arabia in an attempt to synthesize the study which puts in them the greatest disaster
Keywords: pluviometric phenomena; water head; pluviometric events